Flora epifitica en Brachiaria spp. - Gonzalez, M.=700 1 Nunes, A.; Alvarez, E.
(Es, En)
Ilus., 10 ref.
Keywords: BRACHIARIA; MALEZAS; EPIFITAS; ASPERGILLUS; FUSARIUM; PENICILLIUM; CLADOSPORIDIUM; CUBA